Diagnostic and therapeutic challenges of diffuse abdominal infantile hemangioma: a case report emphasizing multimodality imaging and multidisciplinary management - Yang, Yan; Yi, Minggang; Zhao, Jianshe (Frontiers in Pediatrics, 2026)
BackgroundDiffuse abdominal infantile hemangioma (DAIH) is an exceptionally rare and life-threatening vascular anomaly, characterized by extensive infiltrative growth. It poses significant diagnostic challenges by mimicking malignancy and therapeutic difficulties due to involvement of critical structures. This case highlights the pivotal role of multimodality imaging and a multidisciplinary approach in its management.Case descriptionAn 8-month-old female infant presented with abdominal distension and a history of hematochezia. Multimodality imaging (ultrasound, CT, and MRI) revealed an extensive, infiltrative vascular mass involving the mesentery and small bowel wall. Key findings included marked arterial enhancement, persistent venous pooling, flow voids, and secondary hemodynamic changes (portal/hepatic vein dilatation, aortic narrowing, and pulmonary hypertension). Given the lesion's unresectability and high embolization risk, ultrasound-guided biopsy was performed, confirming GLUT-1 positive infantile hemangioma. Oral propranolol therapy was initiated, leading to a dramatic reduction in lesion size and vascularity on follow-up imaging, along with resolution of pulmonary hypertension.ConclusionsThis case underscores the characteristic imaging spectrum of DAIH, which radiologists must recognize to avoid misdiagnosis as malignancy. It reaffirms that a multidisciplinary strategy—centered on imaging-guided biopsy and propranolol as first-line therapy—can optimize outcomes even in severe cases, establishing a modern standard of care for such complex vascular anomalies.